![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a^2-10a+25-4b^2\)
\(=\left(a^2-2.a.5+5^2\right)-\left(2b\right)^2\)
\(=\left(a-5\right)^2-\left(2b\right)^2\)
\(=\left(a-2b-5\right)\left(a+2b-5\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(x^2-y^2+6x+9\)
\(=\left(x^2+6x+9\right)-y^2\)
\(=\left(x+3\right)^2-y^2\)
\(=\left(x-y+3\right)\left(x+y+3\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(=5^{^2}.\left(x+5\right)^2-3^2.\left(x+7\right)^2\)
\(=\left(5x+25\right)^2-\left(3x+21\right)^2\)
\(=\left(5x+25+3x+21\right)\left(5x+25-3x-21\right)\)
\(=\left(8x+46\right)\left(2x+4\right)\)
\(=4\left(2x+23\right)\left(x+2\right)\)
= 52 ( x + 5)2 - 32 (x +7)2
=[ 5 ( x +5) ]2 - [ 3 ( x + 7) ]2
= ( 5x + 25)2 - ( 3x + 21)2
= ( 5x + 25 - 3x - 21) - ( 5x + 25 + 3x + 21)
= ( 2x +4) - ( 8x +46)
= -6x - 42
= -6 ( x + 7)
![](https://rs.olm.vn/images/avt/0.png?1311)
1/\(\left(x^2-25\right)^2-\left(x-5\right)^2\)
<=>\(\left[\left(x-5\right)\left(x+5\right)\right]^2-\left(x-5\right)^2\)
<=>\(\left(x-5\right)^2\left[\left(x+5\right)^2-1\right]\)
2/\(\left(4x^2-25\right)^2-9\left(2x-5\right)^2\)
<=>\(\left[\left(2x-5\right)\left(2x+5\right)\right]^2-9\left(2x-5\right)^2\)
<=>\(\left(2x-5\right)\left[\left(2x+5\right)^2-9\right]\)
#hoctot<3#
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\left(x^2-2x+1\right)-\left(y^2+2y+1\right)\)
\(=\left(x-1\right)^2-\left(y+1\right)^2\)
\(=\left(x-y-2\right)\left(x+y\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(4x^2-4xy+y^2-9\)
\(=\left(2x-y\right)^2-3^2\)
\(=\left(2x-y+3\right)\left(2x-y-3\right)\)
b) \(x^2-36+4xy+4y^2\)
\(=\left(4y^2+4xy+x^2\right)-36\)
\(=\left(2y+x\right)^2-6^2\)
\(=\left(2y+x+6\right)\left(2y+x-6\right)\)
c) \(9x^2-12xy-25+4y^2\)
\(=\left(9x^2-12xy+4y^2\right)-25\)
\(=\left(3x-2y\right)^2-5^2\)
\(=\left(3x-2y+5\right)\left(3x-2y-5\right)\)
d) \(25x^2+10x-4y^2+1\)
\(=\left(25x^2+10x+1\right)-4y^2\)
\(=\left(5x+1\right)^2-\left(2y\right)^2\)
\(=\left(5x+2y+1\right)\left(5x-2y+1\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
1. \(4x^2-2x-3y-9y^2\)
\(=\left(2x\right)^2-\left(3y\right)^2-\left(2x+3y\right)\)
\(=\left(2x-3y\right)\left(2x+3y\right)-\left(2x+3y\right)\)
\(=\left(2x+3y\right)\left(2x-3y-1\right)\)
2. \(x^2-25=6x-9\)
\(\Rightarrow x^2-6x+9=25\)
\(\Rightarrow\left(x-3\right)^2=25\)
\(\Rightarrow\orbr{\begin{cases}x-3=5\\x-3=-5\end{cases}}\Rightarrow\orbr{\begin{cases}x=8\\x=-2\end{cases}}\)
phân tích thành nhân tử
9-25^2
=32-252
=(3-25).(3+25)
=-22.28